Tracer Study as an Effort to Improve Alumni Careers in Kadiri University Job Placement Service - Safi'i, Imam; Priyantoro, Priyo (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2019)
One indicator of the success of higher education running a higher education system, is the success of alumni in the world of work. One way to find out the condition of alumni is to do a tracer study. Tracer study or alumni tracking is information gathering activities of alumni regarding the competencies needed by stakeholders as material for the process of improving education. Tracer study is conducted for alumni who have graduated for two years because it is considered that time has described the condition of alumni in the world of work. The purpose of this research is to find out (1) Transition of graduates from the world of education to the world of work such as (waiting period of work, the first job search process, the last work situation); (2) Alumni assessment of the contribution of higher education in obtaining competencies; (3) Vertical alignment and horizontal felt by alumni. This type of research is a quantitative descriptive study with a cross-sectional approach, with the stages, starting from the Development of Concepts and Instruments, data collection, and data processing and analysis. The target population is 2419, with the total contactable population of 955 (target subjects), of which 195 alumni are willing to fill in the questionnaire and serve as respondents. The results showed the average of alumni getting a job was six months with the largest percentage of job search done through relations with a percentage of 51.28%, and most types of workplaces were private companies with 46%. While the highest level of competence obtained by alumni is communication with vertical alignment level, 67% of respondents stated the same and 85.6% stated aligned related to horizontal alignment.